Enhanced electrical and mechanical properties of rubber/graphene film through layer-by-layer electrostatic assembly. (1st April 2016) - Wang, Lei; Wang, Wencai; Fu, Ye; Wang, Junjun; Lvov, Yuri; Liu, Jun; Lu, Yonglai; Zhang, Liqun
Abstract: Despite a large amount of work have been carried out to prepare polymer/graphene hybrid nanocomposites, preparing rubber composites filled with graphene oxide via layer-by-layer (LBL) electrostatic self-assembly has not yet been reported. In this work, free-standing conductive multilayer film of (PEI/XNBR/PEI/GO)30 (30 is referred to the number of deposition cycles) was fabricated on glass substrate through alternative LBL self-assembly with graphene oxide (GO), carboxylic acrylonitrile butadiene rubber (XNBR) latex, and polyethyleneimine (PEI). During the self-assembly process, negatively charged carboxyl groups on XNBR latex and GO sheets can be electrostatically bound by positively charged amino groups from PEI molecules. After thermal treatment, XNBR latex particles in each layer are gradually mixed together and became a continuous rubber film layer, and partial ionic bonds among XNBR latex, PEI and GO sheets are changed into covalent amide bonds. The formation of the multilayer XNBR/graphene film with ordered arrangement of GO sheets and XNBR latex layers was demonstrated by atomic force microscopy (AFM) and scanning electron microscopy (SEM). The obtained XNBR/graphene film exhibited a significant improvement in mechanical properties, namely, 192% increase of the tensile strength and 215% increase of the elastic modulus. Besides, electrical conductivity of the prepared multilayer film reached 8.2E-03 S cm −1 after thermal reduced reaction. Hopefully, this prepared multilayer film may be potentially used as an elastomeric conductive material.